PENGGUNAAN EKSTRAK DAUN JAMBU BIJI (Psidium guajava Linnaeus) SEBAGAI IMUNOSTIMULAN IKAN MAS (Cyprinus carpio L) YANG DIINFEKSI MOTILE AEROMONAS SEPTICEMIA - Rissa Amelia; Esti Harpeni; Hilma Putri Fidyandini (Journal of Aquatropica Asia, 2021)
This study aims to analyze the effect of the various concentration of guava leaf extract (Psidium guajava Linnaeus) on the prevention of Motile Aeromonas Septicemia disease in common carp (Cyprinus carpio Linnaeus). In a total of 150 common carp, length 9-11 cm with a density of 10 carps/aquarium. This study used a completely randomized design through 5 treatments, each treatment has 3 replications, namely (K+) consists of without guava Psidium guajava leaf extracts and without bacteria-infection Aeromonas hydrophila, (K-) consists of without guava Psidium guajava leaf extracts with bacteria-infection Aeromonas hydrophila, (A) the application of 125 ppm guava Psidium guajava leaf extracts, (B) the application of 250 ppm guava leaf extracts, (C) the application of 500 ppm guava Psidium guajava leaf extracts for 23 days. The parameters observed total of leukocytes, differensial leukocytes, hematocrit levels, erythrocyte, hemoglobin, phagocytic activity (AF), phagocytic index (IF), relative percent survival (RPS), survival rate (SR) and water quality. Data were analyzed with Anova 95% confidence interval and continued with Duncan test. The parameter also showed a significant result (P<0,05) with the application of guava Psidium guajava leaf extracts to the total leukocytes, differensial leukocytes, erythrocyte, hemoglobin, phagocytic activity, phagocytic index and relative percent survival. The results of this research indicate the concentration of 250 ppm guava Psidium guajava leaf extracts is the optimum application to increase common carp non-spesific immune responses.